The Criminal Prosecution: Sporting Event or Quest for Truth? - William J. Brennan Jr. (Washington University Law Quarterly, 1963)
The subject of this Lecture is whether we should extend to criminal prosecutions the civil pre-trial discovery techniques which force both sides of a civil law suit to put all cards on the table before trial, and tend to reduce the chance that surprise or maneuver, rather than truth, may determine the outcome of the trial? Or, as Glanville Williams has asked, shall we continue to regard the criminal trial as “in the nature of a game or sporting contest” and not “a serious inquiry aiming to distinguish between guilt and innocence”?
Keywords: Discovery; Pretrial procedure; Urban transportation -- Federal aid; Criminal procedure